Getting results : the secret to motivating yourself and others - LeBoeuf, Michael; Australian Bureau of Statistics (New York : Berkley, 1985)
A descriptive presentation of some significant national statistics from the 1994 national Aboriginal and Torres Strait Islander survey. Contains a guide to obtaining further information from the survey.
Catalogue no. 4191.0.
Keywords: Aboriginal Australians -- Statistics; Torres Strait Islanders -- Statistics; Aborigines; Statistics